Disc‐electrospun cellulose acetate butyrate nanofibers show enhanced cellular growth performances1. Issue 1 (24th July 2012) - Huang, Chen; Niu, Haitao; Wu, Chunchen; Ke, Qinfei; Mo, Xiumei; Lin, Tong
Abstract: Cellulose acetate butyrate nanofibers were prepared separately by two electrospinning techniques; a needleless electrospinning using a disc as spinneret and a rotary drum as collector and a conventional needle electrospinning using a rotary drum as collector. Compared to the needle‐electrospun nanofibers, the disc‐electrospun nanofibers were coarser with a wider diameter distribution. Both fibers had a similar surface morphology and they showed no difference in chemical components, but the disc‐electrospun nanofibers were slightly higher in crystallinity. The productivity of disc electrospinning was 150 times larger than that of needle electrospinning. The disc‐electrospun nanofiber mats were found to have a three dimensional fibrous structure with an average pore size of 9.1 μm, while the needle‐electrospun nanofibers looked more like a two‐dimensional sheet with a much smaller average pore size (3.2 μm). Fibroblasts and Schwann cells were cultured on the fibrous matrices to assess the biocompatibility. The disc‐electrospun nanofiber webs showed enhanced cellular growth for both fibroblasts and Schwann cells, especially in a long culture period. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A:115–122, 2013.